Understanding pragmatic paradoxes: when contradictions become paralyzing and what to do about it - Cunha, Miguel Pina e (2022)
Integration of paradoxes, comprising interdependent yet contradictory tensions such as those of stability and change, learning and performing, or the individual and the collective, have been recently recognized as sources of synergy and competitive advantage. When adequately navigated, paradoxes may promote innovation, favoring generative complementarities. Not all paradoxes, however, have such generative effects. Pragmatic paradoxes, or managerially imposed contradictory demands that must be disobeyed to be obeyed, tend create paralyzing catch-22 situations. Like weeds, pragmatic paradoxes may also grow alongside the generative type. We explore the conditions in which pragmatic paradoxes become invasive in organizations, identify their main characteristics and symptoms, discuss their roots, and recommend potential approaches for their eradication.